Nutritional influences on growth and onset of puberty in Boran and Boran X Friesian bulls in Ethiopia - Tegegne, Azage; Entwistle, K.W.; Mukasa-Mugerwa, E. (Elsevier, 1992)
Outlines results of a study carried out in Ethiopia, to determine the effect of dry season supplementation on bull's growth and fertility, hence 27 Boran and 37 Boran X Friesian crossbred bulls were weaned at 6 months of age and were randomly assigned to either a dry season supplementary feed containing 16 percent crude protein or control groups. Data were collected on body weight, wither height and scrotal circumference at monthly intervals. The bulls received gonadotropin releasing hormone at 2-month intervals, and plasma testosterone responses were determined; semen was collected at monthly intervals by electroejaculation.